Biharmonic B-general helices according to Bishop frame in Heisenberg group Heis 3 - Körpinar, T.; Turhan, E.; Asil, V. (My University, 2011)
In this paper, we study biharmonic B-general helices according to Bishop frame in the Heisenberg group Heis 3. We give necessary and sufficient conditions for B-general helices to be biharmonic according to Bishop frame. We characterize the biharmonic B-general helices in terms of Bishop frame in the Heisenberg group Heis 3. Additionally, we illustrate our main theorem. © IDOSI Publications, 2011.
Keywords: Biharmonic curve; Bishop frame; Heisenberg group